From Theory to Practice: The Impact of Task-Based Learning on Grammar Proficiency in EFL Teaching - Ananda, Jumriah; Asiza, Nur (Institut Agama Islam Negeri Palopo, 2025)
This study addressed the persistent challenge in English language teaching where students have theoretical knowledge of grammar but struggle to apply it in practical communication. The research aimed to analyse the effectiveness of Task-Based Language Teaching (TBLT) in improving the grammar skills of first-year English Education students at IAIN Parepare. Using a quantitative pre-experimental design with a one-group pretest-posttest approach, the study involved 16 first-year students selected through purposive sampling. The intervention consisted of five TBLT sessions structured around a three-phase framework (pre-task, task cycle, language focus) targeting five grammatical tenses (Simple Present, Present Continuous, Simple Past, Simple Future and Present Perfect). Data were collected via structured oral interviews before and after the intervention, with responses scored using a five-point grammatical accuracy rubric. Results showed a statistically significant improvement in students' grammatical accuracy, with mean scores increasing from 46.50 (Average category) to 66.75 (Good category), representing a 43.5% improvement (p < 0.05). Analysis of individual tenses showed that tenses commonly used in everyday communication (Simple Present, Present Continuous) showed greater improvement (44.1% and 43.4% respectively) than more complex tenses such as Present Perfect (39.7%). The results suggest that TBLT effectively bridges the gap between declarative and procedural grammar knowledge by providing authentic communicative contexts for grammar practice, although complex grammatical structures may require extended practice and additional form-focused instruction for mastery.